Produção e caracterização de recobrimentos de carbono-flúor via técnica rf-PECVD a partir do gás tetrafluoretano - Nery, Ricardo de Pádua Oliveira Sá (2017)
In this work carbon-fluorine-based coatings deposited by rf-PECVD technique from the low cost, environmentally friendly and commercially available tetrafluoroethane (C2H2F4) gas were produced. Surface, mechanical, structural and tribological coatings properties were analyzed according to the deposition electrodes (anode and cathode), deposition pressure (0,05 – 0,2 torr) and deposition energy (-150 – -750 V to cathode and 5 – 60 W to anode). Subimplantion model associated with substitution of hydrogen by fluorine took part in cathode deposition. Fluorinated amorphous diamond-like carbon coatings with 1 – 5,5 GPa hardness, 10 – 40 GPa elastic modulus, 0,55 GPa mean internal stress and 0,35 ± 0,11 dynamic friction coefficient were produced in the cathode electrode. Activated growth model associated with plasma polymerization in continuous mode took part in anode deposition. A plasma polymer, probably the well-known teflon-like polymer, with virtually no internal stress, 0,2 – 1,73 GPa hardness, 4,6 – 15,5 GPa elastic modulus and 0,62 ± 0,16 dynamic friction coefficient were produced in the anode electrode. In both electrodes, high deposition rates (1800 Å/minute), low roughness coatings and deposition parameters control ability make interesting new C2H2F4 deposition by rf-PECVD technique